Հանրահաշիվ Դասարանական և Տնային աշխատանքներ

166688956_115796630485198_2004540011954970185_n

1) 8(x+3)=48

8x+24=48

8x=48-24

8x=24

x=2

2) 5(y-1)=30

5y-5=30

5y=30+5

5y=35

y=7

3) (z+2)*4=60

4z+8=60

4z=60-8

4z=52

z=13

4) (2x-1)*9=45

18x-9=45

18x=45+9

18x=54

x=3

5) 3(a+5)=36

3a+15=36

3a=36-15

3a=21

a=7

6) 14=7(b-3)

14=7b-21

14+21=7b

7b=35

b=5

7) 8(2m+5)=72

16m+40=72

16m=72-40

16m=32

m=2

8) 4(15-2x)=20

60-8x=20

-8x=20-60

-8x=-40

x=5

9) (15-4y)*15=45

225-60y=45

225-45=60y

60y=180

y=3

10) -36=2(10-7z)

-36=20-14z

6z=-36

z=-6

11) 6(4+3a)=-48

24+18a=-48

18a=-48-24

18a=-72

a=4

12) 35=-5(1-x)

35=-5-5x

5x=-5-35

5x=-40

x=-8

13) 3(x-5)+8=17

3x-15+8=17

3x=17+15-8

3x=24

x=8

14) 5(y-2)-9=11

5y-10-9=11

5y=11+10+9

5y=30

y=6

15) 6(a+5)-8a=a

6a+30-8a=a

6a-8a+a=-30

-a=-30

16) -2z+7(z+3)=41

-2z+7z+21=41

-2z+7z=41-21

5z=20

z=4

17) 3(7-b)-5=5b

21-3b-5=5b

-3b-5b=-21+5

-8b=-16

b=2

18) 5c+2(7-2c)=11

5c+14-4c=11

5c-4c=11-14

c=-3

19) 8(10-x)=5(x+3)

80-8x=5x+15

-8x-5x=15-80

-13x=-65

x=5

20) 6(7a-3)=64+a

42a-18=64+a

42a-a=64+18

41a=82

a=2

21) 6(x-3)+2(x+2)=10

6x-18+2x+4=10

6x+2x=10+18-4

8x=24

x=3

22) 5(y-1)-4(y-3)=-20

5y-5-4y+12=-20

5y-4y=-20+5-12

y=-27

23) 5(x+1)+6(x+2)=9(x+3)

5x+5+6x+12=9x+27

5x+6x-9x=27-5-12

2x=10

x=5

24) 6(x+1)+3(8-x)=11(x+2)

6x+6+24-3x=11x+22

6x-3x-11x=22-6-24

-8x=-8

x=1

25) 7(3y+7)+5(y-3)-2(y-8)=2

21y+49+5y-15-2y+16=2

21y+5y-2y=2-49+15-16

24y=-48

y=-2

26) 4(5y+2)-7(1-2y)+5(8-y)=128

20y+8-7+14y+40-5y=128

20y+14y-5y=128-8+7-40

29y=87

y=3

27) 3(2z-1)-5(z-3)+6(3z-4)=83

6z-3-5z+15+18z-24=83

6z-5z+18z=83+3-15+24

19z=95

z=5

28) 4(a+2)-7(2a-1)=30-9(3a-4)

4a+8-14a+7=30-27a+36

4a-14a+27a=30+36-8-7

17a=51

a=3

29) 8(3y-1)-9(5y-11)=30-2(7-2y)

24y-8-45y+99=30-14+4y

24y-45y-4y=30-14+8-99

-25y=-75

y=3

30) 10(8-3z)+11(z-4)-3(4-3z)=4

80-30z+11z-44-12+9z=4

-30z+11z+9z=4-80+44+12

-10z=-20

z=2

31) 19-8(7-4x)=5(8x-2)-7(4x+1)

19-56+32x=40x-10-28x-7

32x-40x+28x=-10-7-19+56

20x=20

x=1

32) -5(12x-7)=19-3(2x+1)-7(6x-1)

-60x+35=19-6x-3-42x+7

-60x+6x+42x=19-3+7-35

-12x=-12

x=1

33) 3(2z+1)-4(1-3z)=16+5(6z-7)

6z+3-4+12z=16+30z-35

6z+12z-30z=16-35-3+4

-12z=-18

z=1 1/2

34) 10(3b-2)-39=3(5b+2)-5(11-4b)

30b-20-39=15b+6-55+20b

30b-15b-20b=6-55+20+39

-5b=10

b=-2

Թողնել պատասխան

Fill in your details below or click an icon to log in:

WordPress.com Logo

You are commenting using your WordPress.com account. Log Out /  Փոխել )

Twitter picture

You are commenting using your Twitter account. Log Out /  Փոխել )

Facebook photo

You are commenting using your Facebook account. Log Out /  Փոխել )

Connecting to %s